Application of microwave and ultrasonic demulsification techniques on petroleum based emulsions - Souleyman, Ahmat Issaka (2012)
Although emulsions are very useful and desired products in cosmetic,food and soft drink industries,yet they are considered as troublesome and undesired product in petroleum industries wherein;they eventually need to be broken into pure oil and water.The current demulsification techniques that consist of mainly chemicals together with mechanical, heating and electrical methods are not very good,since chemical for instance are costly and harmful to the environment,mechanical techniques such as gravity settling tank,hydrocyclone vessel,centrifugal separators, and steam stripping are large requiring more space and cost, electrical techniques almost always work in a very high voltage that can easily cause fire via short circuit, the objective of this project is to assess the effectiveness of some other integrated techniques that have not being fully developed,namely microwave and ultrasonic techniques integrated with chemicals for the purpose of reducing or eliminating the chemical demusifiers, another objective of the current project is also to formulate a stable emulsion that resemble the natural emulsion,this in turn generated another interesting objective of decolorizing the crude oil for microscopic droplet size analysis of heavy oil.A massive screening was carried out to fix the optimal parameters in making a stable w/o emulsios these including stirring intensity, emulsifiers’ types and concentration and water volume fraction,the results showed that the optimal parameters to produce w/o emulsions were 0.25% (v/v) emulsifiers concentration(Span 80)with mixing speed of 1600 rpm for 7 minutes.From the demulsification process it was observed that when chemical assisted microwave was used a demulsifiers’ concentration of 0.1% with two minutes irradiation time gave the best separation efficiency for 50-50% w/o emulsions, while for 20-80 % w/o emulsions; 0.05% demulsifiers concentration and 3.5 minutes irradiation time gave the best water separation of 60%.Chemical assisted ultrasonic also was found to be very effective, when emulsions were sonicated with 0.7%(v/v)of demulsifiers. Hence ultrasonic-chemical integrated system gave the highest separation rate for water-in-crude oil emulsions which reached 97% at power level of 3,compare to microwave-chemical integrated system which gave maximum separation efficiency of 87% at the aforementioned concentration of 0.1%.However when the demulsifiers were increased to 0.7% microwave had given a maximum separation of 96%,Microwave also was tested in some other real industrial emulsions namely Slop oil emulsion and waste coolant emulsion and gave very high separation as expected.Fundamentally the basic mechanism behind the effectiveness of microwave demulsification is that the electromagnetic wave that induce the water molecules to move as trying to rearrange themselves with the wave in two distinct mechanisms known as ionic conduction and dipole rotation that would eventually convert the wave energy into heat generated within the water molecules,while for ultrasonic demulsification it is normally governed by the pressure exerted by the sound wave on the droplets as they travel through the emulsion medium, hence the compression refraction form of the wave motion would make the suspended water droplet to aggregate on the nodes and coalesce.